2014
DOI: 10.1111/joor.12218
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fixed orthodontic appliances on masticatory and swallowing threshold performances

Abstract: To test the hypothesis that treatment with orthodontic appliances disturbs masticatory and swallowing performances. Twenty-seven subjects with malocclusions requiring orthodontic treatment were included in this prospective study. The masticatory and swallowing performances were evaluated at five different times: before bracket placement (T0), immediately after archwire placement (T1), 48 h after archwire placement (T2), 30 days after archwire placement (T3) and 3 months after the initial appointment (T4). Mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…23 The pain and discomfort experienced by the participants in the first and twelfth months of treatment may also have contributed to issues during eating. 27,26 The results presented in this study that investigated the perception of pain levels and chewing impairment among adolescents submitted to orthodontic treatment with fixed appliances may be useful for improving the clinical performance of orthodontists. Orthodontic treatment deliverers should advise patients and their parents/caregivers on the likelihood of pain and chewing impairment during the course of the treatment and inform that those issues should be interpreted as common events during orthodontic therapy.…”
Section: Bzmw=brazilian Minimum Wagementioning
confidence: 99%
See 1 more Smart Citation
“…23 The pain and discomfort experienced by the participants in the first and twelfth months of treatment may also have contributed to issues during eating. 27,26 The results presented in this study that investigated the perception of pain levels and chewing impairment among adolescents submitted to orthodontic treatment with fixed appliances may be useful for improving the clinical performance of orthodontists. Orthodontic treatment deliverers should advise patients and their parents/caregivers on the likelihood of pain and chewing impairment during the course of the treatment and inform that those issues should be interpreted as common events during orthodontic therapy.…”
Section: Bzmw=brazilian Minimum Wagementioning
confidence: 99%
“…The clinician should persuade the adolescent to carry out adequate hygiene and instruct them to maintain a slow and careful mastication, to cut the food into smaller pieces and to avoid hardy and sticky foods, which will ease chewing and will reduce the likelihood of complications, such as device breakage and episodes of pain. 26 In addition to that, the orthodontist should be careful during the brackets and bands placement and should also check during follow-up appointments whether the orthodontic wire is long in order to avoid the appearance of traumatic ulcers. 29 Last but not least, orthodontists must always be available to assist patients with questions regarding the treatment and in case of emergency.…”
Section: Bzmw=brazilian Minimum Wagementioning
confidence: 99%
“…The Masticatory Performance (MP) is an indicator of oral function capabilities that measures the comminution of food attainable under standardized testing conditions 1 . It is possible to generalize that the MP quantifies the changes of a given characteristic in the food bolus during mastication; for example, the average particle size of hard/brittle food such as peanuts 2 or Optosil 3 , or the mixture of colours of a chewing gum 4 . The MP is commonly used to assess the impact of prosthetic dental treatments 57 ; besides, previous studies have associated numerous health disorders with a decline in MP, such as the orofacial impairments following stroke 8,9 , the Metabolic Syndrome 10 , among others 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic pain, perceived as a soreness and pressure sensation (Long et al , ), is prevalent among 72–100% of orthodontic patients (Long et al , ; Asiry et al , ). Being a by‐product of orthodontic treatment, orthodontic pain could cause speech disturbance (Khattab et al , ), emotional stress (Yozgatian et al , ), and masticatory interference (Magalhaes et al , ; Gameiro et al , ), thereby decreasing health‐related quality of life of those who suffer (Wang et al , ). Moreover, it has been reported that orthodontic pain could reduce patients’ compliance during treatments (Sergl et al , ) and is a major reason for treatment terminations at initial treatment stages (Polat, ).…”
Section: Introductionmentioning
confidence: 99%